Bifurcation analysis of a diffusion-ODE model with Turing instability and hysteresis - Li, Ying; Marciniak-Czochra, Anna; Takagi, Izumi (Hiroshima mathematical journal, 2017)
This paper is devoted to the existence and (in)stability of nonconstant steady-states in a system of a semilinear parabolic equation coupled to an ODE, which is a simplified version of a receptor-ligand model of pattern formation. In the neighborhood of a constant steady-state, we construct spatially heterogeneous steady-states by applying the bifurcation theory. We also study the structure of the spectrum of the linearized operator and show that bifurcating steady-states are unstable against high wave number disturbances. In addition, we consider the global behavior of the bifurcating branches of nonconstant steady-states. These are quite different from classical reaction-diffusion systems where all species diffuse.
Gesehen am 26.07.2017